PENDEKATAN LEAN MANUFACTURING UNTUK MENGURANGI WASTE PADA LANTAI PRODUKSI CRUMB RUBBER DI PT DJAMBI WARAS JUJUHAN - Meldia Ananda; Tri Ernita; Faridatul Azizah (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
PT Djambi Waras Jujuhan is a company engaged in the production of crumb rubber. During the production process there is still waste or waste, namely defect, waiting and transportation. To reduce waste, a lean manufacturing approach is carried out, so that it is known the causes of waste on the production floor with VALSAT, and provides suggestions for improvements with FMEA. Based on the results of the study, it is known that the causes of waiting are sluggish workers, inaccurate, trouble in the engine, only forklift 1, and uncertain weather. The cause of the defect is the lack of accuracy, fatigue, creeper diameter shrinking, blunt creeper rool, improper knife settings, improper temperature regulation, dirty raw material, thick blanket, high raw material moisture content, and rain. The cause of transportation is that the work procedure is not carried out properly, the worker is only 1, and the forklift is only 1. From FMEA it is known that the RPN value of each waste is waiting for 294, the defect is 252, and transportation is 36. To reduce waste is recommended to reduce energy work, admonishing workers who do not comply with regulations, choosing workers who have good skills in accordance with their fields of work, increasing control actors, improving work methods, and adding transportation equipment.